2013
DOI: 10.1016/s1734-1140(13)71069-7
|View full text |Cite
|
Sign up to set email alerts
|

Exendin-4 and GLP-1 decreases induced expression of ICAM-1, VCAM-1 and RAGE in human retinal pigment epithelial cells

Abstract: The obtained results indicate that both GLP-1 and exendin-4 by decreasing the expression of RAGE in HRPE can make these cells more resistant to circulating AGEs, and decreased expression of circulating VCAM-1 and ICAM-1, can be the result of anti-inflammatory properties of incretins and decreased expression of RAGE.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…An in vitro study by Dorecka and colleagues [44] demonstrated that treatment with GLP-1 (100 nM) inhibited TNF-α-induced expression of receptors for advanced glycation end products (RAGE), ICAM-1 and VCAM-1 in cultured human retinal pigment epithelial cells, suggesting that attenuation of TNF-α might be a mechanism for the action of GLP1. In line with this conclusion, the present study found that TNF-α expression was attenuated at the level of mRNA in cardiac tissues by GLP1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…An in vitro study by Dorecka and colleagues [44] demonstrated that treatment with GLP-1 (100 nM) inhibited TNF-α-induced expression of receptors for advanced glycation end products (RAGE), ICAM-1 and VCAM-1 in cultured human retinal pigment epithelial cells, suggesting that attenuation of TNF-α might be a mechanism for the action of GLP1. In line with this conclusion, the present study found that TNF-α expression was attenuated at the level of mRNA in cardiac tissues by GLP1 treatment.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to these tissues, emerging data suggest that GLP-1-based therapies also showed anti-inflammatory effects on the liver, vascular system including aorta and vein endothelial cells, brain, kidney, lung, testis, and skin by reducing the production of inflammatory cytokines and infiltration of immune cells in the tissues [ 17 , 21 25 ]. Thus, GLP-1 therapy may be beneficial for the treatment of chronic inflammatory diseases including nonalcoholic steatohepatitis, atherosclerosis, neurodegenerative disorders, diabetic nephropathy, asthma, and psoriasis [ 14 , 26 32 ]. Drugs which are GLP-1 receptor agonists or DPP-4 inhibitors are shown in Table 1 .…”
Section: Introductionmentioning
confidence: 99%
“…Further, vildagliptin treatment was found to completely inhibit the increase in angiogenic, inflammatory and thrombogenic gene expression (VEGF, ICAM-1 and PAI-1) in the retinas of OLETF rats [ 151 ]. Exendin-4 and GLP-1 decreased RAGE levels in AGEs-exposed human retinal pigment epithelial cells and made these cells more resistant to harmful effects of AGEs, leading to suppression of ICAM-1 and VCAM-1 levels [ 152 ], thus suggesting the clinical utility of DPP-4 inhibitors and/or GLP-1-based medicine for the treatment of obese type 2 diabetes, including diabetic retinopathy. The effects of DPP-4 inhibition on microvascular complications were recently thoroughly described by Avogaro [ 153 ].…”
Section: Introductionmentioning
confidence: 99%